1987
DOI: 10.2527/jas1987.653738x
|View full text |Cite
|
Sign up to set email alerts
|

Justification of Unilateral Hysterectomy-Ovariectomy as a Model to Evaluate Uterine Capacity in Swine

Abstract: Experimental objectives were to measure the effect of ovulation rate on litter size at 86 d of gestation and at farrowing in 110 unilaterally hysterectomized-ovariectomized (UHO) gilts and in 142 intact, control gilts and to evaluate postnatal survival and development of progeny. Surgery (UHO) was performed on gilts 8 to 12 d following first estrus. Control and UHO gilts were mated and then randomly assigned to be slaughtered at d 86 of gestation or allowed to farrow. Gilts scheduled to farrow were observed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
124
1
6

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(135 citation statements)
references
References 13 publications
4
124
1
6
Order By: Relevance
“…The observed change in litter size was .20 • .20 at 50 d of gestation and .19 +_ .14 at birth. The agreement between these values indicates a fairly high genetic correlation between litter size at the two stages even though a sizeable loss in number of fetuses occurs late in gestation (Christenson et al, 1987).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The observed change in litter size was .20 • .20 at 50 d of gestation and .19 +_ .14 at birth. The agreement between these values indicates a fairly high genetic correlation between litter size at the two stages even though a sizeable loss in number of fetuses occurs late in gestation (Christenson et al, 1987).…”
Section: Discussionsupporting
confidence: 51%
“…Therefore, the rate of decline in embryo (fetal) survival rate did not completely offset the increase in ovulation rate. Christenson et al (1987) reported that fetal loss is sizeable late in gestation. If some of the variation in this loss is genetic, selection for an index as in this experiment probably would be more effective if fetuses or piglets could be counted closer to or at farrowing time.…”
Section: Discussionmentioning
confidence: 99%
“…However, only Town et al (2004) and studied the effects of intrauterine crowding on muscle development using these experimental approaches. Compared with OL sows, HO sows have only half the uterine space, whereas the overall ovulation rate is similar for both experimental models (Christenson et al, 1987). Therefore, combining the HO and OL experimental model makes uterine conditions regarding space and nutrient availability per fetus even more divergent and allows to better determine the effects of intrauterine crowding on fetal development and myogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to differences in the populations studied, but may also indicate that uterine competition tends to increase throughout gestation. This increased competition has been evidenced by superovulation and embryo transfer experiments (Dziuk, 1968;Pope et al, 1972;Webel and Dziuk, 1974) or more recently by experiments on unilaterally hystero-ovariectomized females (Christenson et al, 1987;Legault et al, 1995). Bennett and Leymaster (1989) (Santacreu et al, 1990).…”
mentioning
confidence: 99%